Potassium tert-Butoxide Promoted Synthesis of 4,5-Diaryl-2H-1,2,3-triazoles from Tosylhydrazones and Nitriles - Qiu, Shanguang; Chen, Yuxue; Song, Xinming; Liu, Li; Liu, Xi; Wu, Luyong (Synlett, 2020)
Intermolecular cycloaddition of tosylhydrazones with nitriles was investigated. t-BuOK was shown to be an excellent base for increasing the effectiveness of the reaction in this protocol, and homocoupling of the tosylhydrazones was significantly inhibited by using xylene as a solvent. Through this transformation, a variety of 4,5-diaryl-2H-1,2,3-triazoles were prepared in good to excellent yields and with high purities. The process is azide-free and transition-metal-free.
Keywords: triazoles; tosylhydrazones; cycloaddition; potassium butoxide